RETRACTED: Parallel Encryption With Digit Arithmetic Of Covertext Model Using Duplicated Covertext - Murti, Hari; Supriyanto, Edy; Redjeki, Rara; Ardhianto, Eka (Inspiration: Jurnal Teknologi Informasi dan Komunikasi, 2022)
Steganography is the art and science of writing hidden messages or hiding messages in such a way that, apart from the sender and the recipient, no one knows or is aware that there is a secret message (it does not appear that there is a hidden message. Furthermore, public key cryptography is the type of cryptography that using two interrelated keys, namely the public and private keys. Cryptography and steganography techniques have an important role in securing information. Parallel Encryption with Digit Arithmetic of Covertext (PDAC) encryption model adopts cryptography and steganography for securing messages. The accuracy of the number of covertext in the PDAC affects whether the PDAC works. If the number of PDAC covertext does not match, then the encryption process will be imperfect. This study aims to close the PDAC gap. The proposed model adopts the repeated use of covertext. Covertext loops applied in PDAC can process information security. Another advantage obtained is that this modification makes it easier for users to use PDAC without having to meet the minimum covertext requirement.